A Pilot Study of Safer Radiation Dosage to the Heart and Its Subregions - Rita Steponavičienė; Justinas Jonušas; Romualdas Griškevičius; Jonas Venius; Saulius Cicėnas (Medicina, 2021)
Background and Objectives: The real impact of ionizing radiation on the heart and poorer overall survival for patients with non small cell lung cancer (NSCLC) remains unclear. This study aims to determine the safe dose constraints to the heart’s subregions that could prevent patients’ early non-cancerous death and improve their quality of life. Methods and Materials: A retrospective cohort study was performed containing 51 consecutive patients diagnosed with stage III NSCLC and treated using 3D, Intensity-modulated radiation therapy (IMRT), and Volumetric modulated arc therapy (VMAT) radiotherapy. For a dosimetric analysis, these structures were chosen: heart, heart base (HB), and region of great blood vessels (GBV). Dose–volume histograms (DVH) were recorded for all mentioned structures. Maximum and mean doses to the heart, HB, the muscle mass of the HB, and GBV were obtained. V10–V60 (%) parameters were calculated from the DVH. After performed statistical analysis, logistic regression models were created, and critical doses calculated. Results: The critical dose for developing a fatal endpoint for HB was 30.5 Gy, while for GBV, it was 46.3 Gy. Increasing the average dose to the HB or GBV by 1 Gy from the critical dose further increases the possibility of early death by 22.0% and 15.8%, respectively. Conclusions: We suggest that the non-canonical sub-regions of the heart (HB and GBV) should be considered during the planning stage. Additional constraints of the heart subregions should be chosen accordingly, and we propose that the mean doses to these regions be 30.5 Gy and 46.3 Gy, respectively, or less. Extrapolated DVH curves for both regions may be used during the planning stage with care.